Hubungan Peran Pengawas Minum Obat dengan Kepatuhan Antiretrovital Pasien HIV di Rumah Singgah Dukungan Sebaya - Nirwanto Rahim; Elvie F. Dungga; Nur Ayun R. Yusuf; Mirsa Setyawan Ino (An Idea Health Journal, 2024)
Non-adherence to ARV (Antiretroviral) treatment results in patients not recovering and potentially worsening. One effort undertaken by various parties is to HIV in peer support shelters in Gorontalo City. The research method employed quantitative research with a Cross-Sectional design. The population of this study consisted of PLHIV (People Living with HIV/AIDS) in peer support shelters, totaling 50 respondents determined through. Total Sampling technique. Furthermore, the data analysis was conducted using the Chi- Square test. The findings denoted that there was a significant correlation between medication supervisors and antiretroviral adherence among patients with HIV in peer support shelters in Gorontalo City (p=0.006). It is hoped that the findings of this study can be utilized to increase public knowledg that society will better understand aspects related to HIV transmission and treatment.